As humanidades em tempos de neoliberalismo em duas Universidades Latino Americanas - Storck, João Batista (Universidade do Vale do Rio dos Sinos, 2016)
The present research aims to produce a knowledge about the way the University of Vale do Rio dos Sinos (Unisinos), located in Brazil, and the Pontifical Xavierian University, located in Colombia, have developed their institutional documents (Statute 2014, PDI-PPI 2006-2011 for Unisinos, and the Statute 2013, PU 2007-2016, PE 1992-2015 for Xaverian) in the current context. Both documents are permeated by the values of the economic neo-liberalism in a society driven by economic values of the techno-sciences and the techno-market. These universities belong to the Society of Jesus, a religious congregation whose educational field in its roots was structured on the principles and values of the Renaissance Christian humanism. Such is one of their characteristics over the Society’s history. The use of two contexts regarding our theoretical framework, called Policy Cycle Approach, proposed by Stephen J. Ball – Context of Influence and Context of Elaboration –, allows us to visualize, interpret and understand, both in a macro and a micro sense, the movements, joints and trajectories that influence and guide the development of educational policies and proposals. This study employs the Document Analysis Method by André Cellard. This method is divided into two stages: Preliminary Analysis and Analysis. We utilize only four of the five dimensions of the Preliminary Analysis proposed by the author (context, document’s authors, the nature of the text, and key concepts). Using these dimensions, along with the subsequent Analysis employed in conjunction with the Comparative Method in Education, by George Z.F Bereday, from which we used its fourth stage, made it possible to apply the Comparative Analysis of the documents. This methodological triangulation has provided support for showing that the documents studied here are subsidized in their preparation, inspiring and receiving influences from a set of documents issued by both the institutions to which the universities are linked – the Roman Catholic Church and the Society of Jesus – and the documents issued by the governments of the countries where they are located, as well as influences from the decisions and options made as consequences of the identity, mission, and vision of each Higher Education Institutions. However, this inspiration/influence does not occur through a process of simple accommodation or assimilation, but they are re-contextualized, reworked and re-signified at the institutional level, where different factors and related interests intertwine with the identity, mission, and vision of such institutions. The study shows that the institutional documents of the analyzed universities fall within the idea of process and that these two Higher Education Institutions have been implementing a major effort to conjugate, while developing their educational projects and plans, the social Christian humanism, from which they are inheritors, with techno-scientificity on an major challenge of creative fidelity to their institutional principles, seeking to build a techno-scientific humanism.
Keywords: Instituições de educação superior; Companhia de Jesus; Javeriana; Unisinos; Plano de desenvolvimento institucional; Projeto pedagógico institucional; Higher education institutions; Society of Jesus; Xaverian; Unisinos; Institutional development plan; Institutional educational projec; ACCNPQ::Ciências Humanas::Educação